Formulation of microbes inoculum: AMF, PSB and Rhizobium isolated of ex-coal mining site for Acacia crassicarpa Cunn. Ex-benth seedlings - ENNY WIDYATI (Society for Indonesian Biodiversity, 2007)
The shoddier succeed land revegetation particularly caused by least adaptability of the seedlings planted on this site. To encourage their growth and survival rate it can be achieved by means do inoculation with the compatible functional microbes such as rhizobium, Psolubilizing bacteria (PSB) and/or arbuscular-mycorrhiza fungy (AMF). This reserach is aimed to formulate the most compatible inoculant to support the growth of A. crassicarpa seedlings. Compatibility study is carried out in RCB design with 3 replications, each contain 5 seedlings. Height and biomass are accessed to measure the growth responses of the seedlings. The result showed that the best reponse is given by consortia that consist of the three kinds of these microbes. This increase the shoot biomass (137%) compare to the control. The consortia also improved N 164%, P 335% and K 167% in the plant tissues. While pure AMF improved absorption of N plants 80%, P 383% and K 51% compare to the control. It is suggested that to prepare the A. crassicarpa seedlings is better inoculated by consortium ofmicrobes or AMF as a sole inoculant.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: AMF, PSB, Rhizobium, revegetation